2017
DOI: 10.5114/ceji.2017.70967
|View full text |Cite
|
Sign up to set email alerts
|

Subpopulations of natural killer-T-like cells before and after surgical treatment of laryngeal cancer

Abstract: IntroductionTumours connected with head and neck comprise about 5% of all tumours. The most frequent histological type of laryngeal carcinoma is squamous cell carcinoma. Different research projects suggest that the role of T lymphocytes might be significant in tumour development. iNKT cells are a new subpopulation of T cells and show cytotoxic activity against tumours. iNKT cells participate in modulating the function of other cells which have anti-tumour properties and secrete cytokines, which have pro-inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 23 publications
2
10
2
Order By: Relevance
“…Interestingly, late-stage cancer patients presented with lower type I NKT cell numbers than early-stage cancer patients with oral squamous cell carcinoma or laryngeal cancer ( 218 , 221 ), suggesting cancer-mediated depletion of NKT cells. After resection of the primary tumor, type I NKT cell numbers did not increase in patients with different cancer types ( 213 , 220 ). By contrast, circulating NKT-like cell numbers were not decreased in patients diagnosed with laryngeal cancer, gastric cancer, or hepatocellular carcinoma ( 91 , 92 , 220 ).…”
Section: The Function and Phenotype Of Nkt Cells In Patients Diagnosementioning
confidence: 94%
See 1 more Smart Citation
“…Interestingly, late-stage cancer patients presented with lower type I NKT cell numbers than early-stage cancer patients with oral squamous cell carcinoma or laryngeal cancer ( 218 , 221 ), suggesting cancer-mediated depletion of NKT cells. After resection of the primary tumor, type I NKT cell numbers did not increase in patients with different cancer types ( 213 , 220 ). By contrast, circulating NKT-like cell numbers were not decreased in patients diagnosed with laryngeal cancer, gastric cancer, or hepatocellular carcinoma ( 91 , 92 , 220 ).…”
Section: The Function and Phenotype Of Nkt Cells In Patients Diagnosementioning
confidence: 94%
“…After resection of the primary tumor, type I NKT cell numbers did not increase in patients with different cancer types ( 213 , 220 ). By contrast, circulating NKT-like cell numbers were not decreased in patients diagnosed with laryngeal cancer, gastric cancer, or hepatocellular carcinoma ( 91 , 92 , 220 ).…”
Section: The Function and Phenotype Of Nkt Cells In Patients Diagnosementioning
confidence: 94%
“…[21][22][23] In addition, recent studies have shown that the population of type-I NKT cells (also known as invariant NKT, or iNKT, cells) with the phenotype CD4-NK1.1 can rapidly secrete a significant amount of IL-17. [24][25][26][27] This rapid cytokine release is possible, at least in part, because of pre-formed cytokine-encoding mRNA, such as for IFN-gamma and IL-4. In this way, these cells can start cytokine secretion faster, without the need for gene transcription.…”
Section: Nkt Cells (%)mentioning
confidence: 99%
“…The results were analyzed with CellQuest Pro software (Becton Dickinson, USA). 26,31 Assessment of regulatory t cells Treg CD4(+)CD25(+)Foxp3(+) cells were prepared for visualization from the fresh blood samples at the time of sample collection. The cells were stained according to the manufacturer's instructions.…”
Section: Assessment Of Basic Lymphocyte Subsets Nk and Nkt-like Cellsmentioning
confidence: 99%
“…A minimum of 10,000 events was acquired and analyzed using CellQuest Software (BD Biosciences, USA). The percentage of cells expressing surface markers were analyzed (Hus et al 2011 ; Klatka et al 2017 ; Nowicka et al 2017 ; Pasiarski et al 2015 ).…”
Section: Methodsmentioning
confidence: 99%